Effects of a fat-rich diet on maximal oxygen uptake and time-to-exhaustion in female triathletes - Titchenal, C. A.; Graybill-Yuen, R. M.; Yuen, K. Q.; Ho, K. W.; Hetzler, R. K. (Medicine & Science in Sports & Exercise, 1998)
Male athletes have been reported to improve VO2max and time to exhaustion after consuming a fat-rich diet. Highly trained female triathletes (N = 5) consumed normal, fat-rich, and carbohydrate rich diets, each for seven days before performing a cycle ergometer test. The fat-rich diet did not improve VO2max, time to exhaustion, or substrate utilization over normal or carbohydrate-rich diets. Implication. The impacts of fat-rich and carbohydrate-rich are insignificant in females whereas they are in males.